Influence of Empowerment and Perceived Organizational Support on Overall Job Satisfaction of Call Centre Employee - Siou, Xiao Jian (2010)
This research is intended to analyze the nature of overall empowerment (EMP), four dimensions of empowerment namely competence (COM), meaning (MEA), impact (IMP), self-determination (SD) and perceived organizational support (POS) in relation to overall job satisfaction (SAT) of call centre front-line employees. The research hypotheses are examined by using a sample of Malaysian call centre front-line employees (n=70). Standard multiple regression is employed to test various hypotheses and examine the extent to which overall empowerment (EMP) four dimensions of empowerment (COM, MEA, IMP, SD) and perceived organizational support (POS) in predicting overall job satisfaction (SAT) in the context of a highly contradicting organizational settings. The research findings indicated that empowerment (EMP), perceived organizational support (POS), competence (COM), and self-determination (SD) are positively related to overall job satisfaction (SAT) of call centre front-line employees. The remaining variables (MEA and IMP) are found not related to overall job satisfaction. Based on these empirical findings, call center management should take proactive measures in the following areas like participative decision making, training and development, job design, open flow of information, organizational structure, and human resource practices to promote overall empowerment (EMP) and perceived organizational support (POS) at the workplace. Some of the advantages for the mentioned initiative include reduced employee turnover, increased overall job satisfaction reduced stress level, and improved job performance among call centre employees. This study takes some initial steps to bridge the knowledge gaps on factors influencing general well-being of call centre FLEs in the context of Malaysia’s call centre. Nevertheless, it’s recommended to incorporate a diverse range of industries into the research, to investigate other potential outcomes of EMP and POS within the same context, to explore the impact of EMP and POS on multiple facets of job satisfaction, cross comparison of the results with a benchmark sample like conventional office employees, incorporation of control variables into the study, and to apply structural equation analysis to adequately address the sophisticated nature contained in the variables of interest.